2004
DOI: 10.1097/01.pec.0000106235.72265.29
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia for Sickle Cell Pain Crisis in a Pediatric Emergency Department

Abstract: A protocol to initiate PCA for sickle cell patients in a pediatric emergency department shortened the time of its initiation and was preferred by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 9 publications
2
30
0
5
Order By: Relevance
“…Hastaların %5'inde bu rakam 10'a kadar çıkabil-mektedir. [3,13] On bir yılı kapsayan çalışmamızda ebeveynlerin %85.2'si yöntemi ikiden fazla kullanıldığını ifade etmişlerdir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Hastaların %5'inde bu rakam 10'a kadar çıkabil-mektedir. [3,13] On bir yılı kapsayan çalışmamızda ebeveynlerin %85.2'si yöntemi ikiden fazla kullanıldığını ifade etmişlerdir.…”
Section: Discussionunclassified
“…[14][15][16] Farklı çalışmalarda iv olarak sürekli infüzyon ve istek dozunun birlikte kullanımı ağrının azaltılmasın-da diğer yöntemlere göre daha etkin olarak saptanmıştır. [2,3,17] Çalışmamızda da kullanıcıların %87.2'si ağrılı krizde ağrının azaltılmasında HKA yöntemini diğer yöntemlere göre daha etkin bulmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…While any undertreatment of pain is not acceptable, this does not appear to explain the high level of parent dissatisfaction. The relatively low level of dissatisfaction with pain treatment may be due to the early transition to patient controlled analgesia at our institution, which has been shown previously to improve satisfaction [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined parent satisfaction with care for one aspect of treatment and found that the initiation of a morphine patient controlled analgesia protocol decreased time between morphine treatments and improved parent satisfaction when initiated in the emergency department [6]. While this study did not use a validated survey, parent satisfaction surveys are now validated and their use widespread [7,8].…”
Section: Introductionmentioning
confidence: 99%